STUDENTS’ POLITENESS STRATEGY IN ONLINE LEARNING CLASSROOM - FitrianiIrma (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
In recent years, online learning platforms have grown rapidly and become one of the most common choices in the world. However, there is still a limited amount of research about the use of politeness strategy in an academic online classroom setting. This research revealed the multicultural students’ preferences for politeness strategy from different countries. It used a qualitative descriptive method and utilized the theory of politeness from Brown and Levinson. The interactions analyzed are teacher-student discussion, peer-to-student feedback, and individual and class discussions on writing format. The research results revealed that the most used strategies were positive politeness strategies (49%), negative politeness strategies (35%), off-record strategies (8%), and bald-on-record strategies (8%). The significant factors influencing these strategies were training and learning contracts that began before class.